2006
DOI: 10.1542/peds.2005-1983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumococcal Conjugate Vaccine on Nasopharyngeal Bacterial Colonization During Acute Otitis Media

Abstract: The heptavalent pneumococcal conjugate vaccine (PCV7) has been shown to reduce the incidence of acute otitis media (AOM) caused by Streptococcus pneumoniae by 34% and reduces the overall incidence of AOM by 6% to 8%. More recent studies have shown increases in the proportion of Haemophilus influenzae and Moraxella catarrhalis in the middle-ear fluid of PCV7-immunized children. There has been no report on the effect of PCV7 on all 3 bacterial pathogens combined, either in the middle-ear fluid or nasopharynx of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 26 publications
2
53
0
2
Order By: Relevance
“…Several studies investigated effects of pneumococcal vaccination on S. aureus, and most did not find any increases in S. aureus colonization associated with PCV7 (4, 5, 13) or PCV9 (14) vacci- (24). Consistent with our findings, studies on the effects of pneumococcal vaccination in healthy children found no increases in carriage of H. influenzae (14,35) or M. catarrhalis (35).…”
supporting
confidence: 90%
“…Several studies investigated effects of pneumococcal vaccination on S. aureus, and most did not find any increases in S. aureus colonization associated with PCV7 (4, 5, 13) or PCV9 (14) vacci- (24). Consistent with our findings, studies on the effects of pneumococcal vaccination in healthy children found no increases in carriage of H. influenzae (14,35) or M. catarrhalis (35).…”
supporting
confidence: 90%
“…A search of VAERS for "Cases where age is under 1 and onset interval is 0 or 1 or 2 or 3 or 4 or 5 or 6 or 7 days and Symptom is otitis media" [63] revealed that 438,573 cases were reported between 1990 and 2011, often with fever and other signs and symptoms of inflammation and central nervous system involvement. One study [64] assessed the nasopharyngeal carriage of S. pneumoniae, H. influenzae, and M. catarrhalis during AOM in fully immunized, partly immunized children with 0 or 1 dose of Pneumococcal Conjugate Vaccine-7 (PCV7), and "historical control" children from the pre-PCV-7 era, and found an increased frequency of M. catarrhalis colonization in the vaccinated group compared to the partly immunized and control groups (76% vs. 62% and 56%, respectively). A high rate of Moraxella catarrhalis colonization is associated with an increased risk of AOM [65].…”
Section: Discussionmentioning
confidence: 99%
“…Widespread administration of this vaccine has resulted in a dramatic reduction in nasopharyngeal colonization by the 7 pneumococcal serotypes included in the vaccine. This has been accompanied by several important changes in the distribution of bacterial pathogens that cause otitis media: (i) a reduction in pneumococcal vaccine serotypes, (ii) a relative increase in pneumococcal nonvaccine serotypes, and (iii) a relative increase in H. influenzae and Moraxella catarrhalis causing nasopharyngeal colonization and otitis media (4,9,36). Two new pneumococcal conjugate vaccines have recently been approved for use, and these include a 13-valent vaccine in the United States and a 10-valent vaccine in Europe in which pneumococcal polysaccharides are conjugated to protein D, a surface protein of H. influenzae (34).…”
Section: Clinical Manifestations Of H Influenzae Infectionsmentioning
confidence: 99%